MONEY POLITIC DALAM SISTEM PEMILU DI INDONESIA - Deni Zein Tarsidi; Ervina Maharani; Muhamad Tegar Fadhilah; Rivan Kusnan Haris Salahudin (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2024)
This study aims to reveal where the causes of money politics arise in national and local elections. This study uses journal data that has been published and selected from 2015 to 2019. The results of this study provide an overview of the practice of buying and selling votes, which has become an uncontrollable part of the implementation of elections, both locally and nationally in Indonesia. National elections and local elections, have been mixed with the behavior of money politics. The more widespread and considered a natural thing, of course, this understanding is very, very wrong. The implication of the very importance of this study is that money politics in elections needs immediate attention and the best countermeasures, because it will guarantee the stability and quality of Indonesian democracy in the future. The methodology used includes: 1) defining a research question; 2) determination of literature sources; 3) determination of keywords for literature search; 4) Selection of literature; and 5) extract data. Based on the methodology, the results obtained contain 10 papers. There are 10 studies that raise the topic of money politics in elections, both local and national, and share knowledge which explains that the contents of the two components become and influence each other. Further studies may be carried out by examining the extent to which money politics may be used as a political expense in campaigns, but is controlled and does not violate the rule of law.